Pengembangan Bahan Ajar Interaktif Berbantuan Anyflip Berbasis Antologi Cerita Pendek pada Materi Cerita Pendek untuk Siswa Kelas XI - Wulan Tiogur Sari Banun Siregar; Nila Safina; Ratna Soraya; Rika Kartika; Ali Ali (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
The limited availability of engaging and technology-integrated teaching materials in short story learning has created challenges in fostering students’ active participation and literary comprehension. This study aimed to develop and evaluate the feasibility and effectiveness of interactive teaching materials assisted by AnyFlip and based on a short story anthology for teaching short story texts to eleventh-grade students at SMAN 2 Lubuk Pakam. Employing a Research and Development approach, the study adopted the Four-D Model consisting of Define, Design, Develop, and Disseminate stages. The research involved a population of 389 students, with 35 students from Class XI-J selected as the sample. The feasibility of the product was assessed through expert validation and user trials involving teachers and students. The results demonstrated that the developed teaching materials achieved a very high level of validity, with material expert evaluations reaching 92.6% and 93.3%, while design expert evaluations reached 89.3% and 80.0%. Teacher assessment yielded a score of 96.0%, and student responses reached 91.0%, both categorized as highly feasible. These findings indicate that the AnyFlip-assisted interactive teaching materials are valid, practical, and highly suitable for supporting the learning of short story texts at the senior high school level.